Improving Case-Based Meningitis Surveillance in 5 Countries in the Meningitis Belt of Sub-Saharan Africa, 2015–2017. (31st October 2019) - Mbaeyi, Sarah A; Lingani, Clement; Diallo, Alpha Oumar; Bicaba, Brice; Ouédraogo-Traoré, Rasmata; Acyl, Mahamat; Gamougame, Kadidja; Coulibaly, Oumou; Coulibaly, Souleymane; Zaneidou, Maman; Sidikou, Fati; Nikiema, Christelle; et al.
Abstract: Background: The MenAfriNet consortium was established in 2014 to support implementation of case-based meningitis surveillance in 5 countries in the meningitis belt of sub-Saharan Africa: Burkina Faso, Chad, Mali, Niger, and Togo. Assessing surveillance performance is critical for interpretation of the collected data and implementation of future surveillance-strengthening initiatives. Methods: Detailed epidemiologic and laboratory data were collected on suspected meningitis cases through case-based meningitis surveillance in participating districts in 5 countries. Performance of case-based surveillance was evaluated through sensitivity of case ascertainment in case-based versus aggregate meningitis surveillance and an analysis of surveillance indicators. Results: From 2015 to 2017, 18 262 suspected meningitis cases were identified through case-based surveillance and 16 262 were identified through aggregate surveillance, for a case ascertainment sensitivity of 112.3%. Among suspected cases, 16 885 (92.5%) had a cerebrospinal fluid (CSF) specimen collected, 13 625 (80.7%) of which were received at a national reference laboratory. Among these, 13 439 (98.6%) underwent confirmatory testing, and, of those tested, 4371 (32.5%) were confirmed for a bacterial pathogen. Conclusions: Overall strong performance for case ascertainment, CSF collection, and laboratory confirmation provide evidence for the quality of MenAfriNet case-based surveillance in evaluating epidemiologic trends and informing future vaccination strategies.